2018
DOI: 10.1186/s13014-017-0942-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s experiences and responses towards an intervention for psychological preparation for radiotherapy

Abstract: BackgroundChildren can experience distress when undergoing radiotherapy as a reaction to being scared of and unfamiliar with the procedure. The aim was to evaluate children’s experiences and responses towards an intervention for psychological preparation for radiotherapy.MethodsA case control design with qualitative content analysis of semi-structured interviews and statistical analysis of anxiety ratings were used for evaluating a strategy for psychological preparation and distraction. Fifty-seven children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In children undergoing radiotherapy, anesthesia ensures adequate immobilization during verification of the patient's position and therapy delivery. With regard to acute and late risks, daily treatment under sedation ( 14 ) is associated with major changes in the child's daily routine, such as the need to fast for several hours ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In children undergoing radiotherapy, anesthesia ensures adequate immobilization during verification of the patient's position and therapy delivery. With regard to acute and late risks, daily treatment under sedation ( 14 ) is associated with major changes in the child's daily routine, such as the need to fast for several hours ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient setup using predetermined couch position and subsequent image guidance enables markless isocenter localization without the need of skin tattoos 6 . The permanent tattoos for conventional radiotherapy could have significant psychosocial impacts on patients, especially breast cancer patients and pediatric patients 8,9 . The implemented method may be useful for tattoo‐less radiation treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The current project is based on previous research conducted by Engvall et al [ 10 ], who developed a digital story describing the RT procedure that was delivered as an application on a tablet designed for children. The participating children suggested that the application could have been more interactive if it had been designed as a game [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current project is based on previous research conducted by Engvall et al [ 10 ], who developed a digital story describing the RT procedure that was delivered as an application on a tablet designed for children. The participating children suggested that the application could have been more interactive if it had been designed as a game [ 10 ]. When designing serious games such as these, there are several aspects that need to be considered, such as the purpose of the game, the end users, the stakeholders in the project, and how the game can engage the players [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%